Money and capacity growth - Stein, Jerome L. (New York : Columbia University Press, 1971)
The book discusses a new growth model that examines a post-Keynesian economies to a growing economy, where the inputs of capital is endogenously determined and growing over time. It also considers the economic growth and stabilization policy as it relates to monetary policy.
includes index
Bibliography: p. [265]-267.
usc 16/6/17
Loans
Keywords: Money; Monetary policy; Economic development